Manpower Planning for Public Health Specialists in Turkey (2013-2023) - Bülent Kılıç; Ceyda Şahan; Hande Bahadır (Turkish Society of Public Health Specialists, 2015)
Abstract Objective: We aim to make a manpower planning forpublic health specialists between the years 2013-2023 in Turkey. Methods: Manpower planning of public health specialists is calculated on the basis of population and institutional necessities. Data is supplied from the databases of HASUDER, ÖSYM, Turkish MoH, YÖK and the Departments of Public Health's. Results: There are 520 public health specialists and 286 public health specialization students in Turkey in 2013. Specialization training is supplied at the 57 departments of public health. Nearly half of the public health specialists' work for Ministry of Health (51%), while 47% of public health specialists works for universities. Totally 2014 specialists are required for Turkey in 2013. This number will be increased to 2365 in 2023. In this situation there is one specialist per 145.000 people in Turkey in 2013, while it had to be one specialist for per 37.537 people. According to our findings there will be a serious lack of public health specialists in 2018. However if public health specialization students quota is increased to 200 per year, public health specialist requirement will be almost completed in the institutions of Ministry of Health in 2023. Conclusions: However, if additional public health specialist requirements of other ministries, international organizations and municipalities are considered not only specialists, public health graduates in MPH and PhD should also definitely be used for manpower planning. Key Words: Public Health Specialist, health manpower planning